Resting state functional connectivity in SLE patients and association with cognitive impairment and blood–brain barrier permeability. (14th June 2022) - Hanly, John G; Robertson, Jason W; Legge, Alexandra; Kamintsky, Lyna; Aristi, Guillermo; Friedman, Alon; Beyea, Steven D; Fisk, John D; Omisade, Antonina; Calkin, Cynthia; Bardouille, Tim; Bowen, Chris; et al.
Abstract: Objective: Extensive blood–brain barrier (BBB) leakage has been linked to cognitive impairment in SLE. This study aimed to examine the associations of brain functional connectivity (FC) with cognitive impairment and BBB dysfunction among patients with SLE. Methods: Cognitive function was assessed by neuropsychological testing ( n = 77). Resting-state FC (rsFC) between brain regions, measured by functional MRI ( n = 78), assessed coordinated neural activation in 131 regions across five canonical brain networks. BBB permeability was measured by dynamic contrast-enhanced MRI ( n = 61). Differences in rsFC were compared between SLE patients with cognitive impairment (SLE-CI) and those with normal cognition (SLE-NC), between SLE patients with and without extensive BBB leakage, and with healthy controls. Results: A whole-brain rsFC comparison found significant differences in intra-network and inter-network FC in SLE-CI vs SLE-NC patients. The affected connections showed a reduced negative rsFC in SLE-CI compared with SLE-NC and healthy controls. Similarly, a reduced number of brain-wide connections was found in SLE-CI patients compared with SLE-NC ( P = 0.030) and healthy controls ( P = 0.006). Specific brain regions had a lower total number of brain-wide connections in association with extensive BBB leakage ( P = 0.011). Causal mediation analysis revealed that 64% of the association between BBB leakage and cognitive impairment in SLE patients was mediated by alterations in FC. Conclusion: SLE patients with cognitive impairment had abnormalities in brain rsFC which accounted for most of the association between extensive BBB leakage and cognitive impairment.